A Report on The Acoustic Conditions of IEQ Laboratory Using ISO 3382-3 - Jason Obadiah (Universitas Multimedia Nusantara, 2017)
Recently, many facilities have completed new laboratories that may be used to assess various measures of Indoor Environment Quality (IEQ) in office spaces. Also recently, a new standard, ISO 3382-3, was released for assessing the effects of speech on IEQ in open plan offices. The aim of this report is to assess one room of the IEQ lab using the ISO 3382-3 standard. It is expected that the data gained will be of help to researchers using the facility in the future. Keywords: ISO 3382-3, Indoor Environment Quality, Acoustics